Paisagem Cultural: discussões contemporâneas por um (novo) olhar para o patrimônio cultural - Luciana de Castro Neves Costa (Universidade do Vale do Rio dos Sinos (UNISINOS), 2016)
From the valorization of the isolated monument to the consideration of the intangible heritage, different constructions of meaning have conditioned the conception of cultural heritage, culminating today in the category of Cultural Landscape. Conceived as a new way of thinking and preserving cultural heritage that comprehends the materiality and immateriality of heritage assets as well as its natural and cultural sphere, the notion of landscape already integrates former discussions on heritage, under different values, in conventions and heritage documents. In the same way, since the institution of IPHAN (National Historic and Artistic Heritage Institute) the notion of landscape has moved between the categories of cultural heritage and natural heritage, and has been consolidated recently as a specific type of heritage asset, the seal of Brazilian Cultural Landscape, that proposes, as a consequence, a new understanding about Brazilian heritage. In this sense, the objective of this article consists in analyzing the process of heritage activation that would consolidate the notion of Cultural Landscape as a new category of heritage asset in Brazil, and the elements comprehended under this typology.